PENGARUH KOMPENSASI DAN DESAIN PEKERJAAN TERHADAP KINERJA KARYAWAN STUDI PT. LANGKAT SAWIT HIJAU PRATAMA - Razi Muliadi; Hasrul Azwar Nasution; Cahyo Pramono (Ensiklopedia of Journal, 2022)
The purpose of this study was to determine the effect of compensation and job design on employee performance in the plantation sector of PT. Langkat Pratama Green Palm Oil, Langkat Province, North Sumatra, Indonesia. This research is an explanation of two independent variables (compensation and work design) and the dependent variable is employee performance. Questionnaires were distributed to employees of PT. Langkat Green Palm Oil Primer. A total of 87 employees from the plantation sector consisting of managerial and non-managerial staff responded to the survey. The survey questionnaire has 22 items covering human resource management practices and employee performance. This study found that compensation and work design have a positive relationship with employee performance. If the plantation sector organization wants to improve employee performance to a higher level, it should focus more on improving compensation and work design. This study helps improve employee performance collectively by implementing human resource practices rather than individually. By understanding the impact of human resource management practices on employee performance, employees can take more appropriate actions to reduce risk. This research will help organizations to find out which practices encourage creativity in organizations. In this study will be able to obtain, and maintain a competitive workforce as a valuable organizational asset. Future researchers can take more human resource practices and examine their impact on employee performance. The questionnaire technique used in this study is a very general technique. Other techniques such as group discussions/interviews can be used to conduct future research. Future researchers may add mediators or other human resource practices and may examine the relationship differently through different methods. Managers can use this data to improve their effectiveness in their organizations by focusing on human resource practices such as compensation and work design that affect employee performance.